DEM modelling of granular materials with real shape morphology - Li, Yang; Otsubo, Masahide; Kuwano, Reiko; Nadimi, Sadegh; Angelidakis, Vasileios (Seisan Kenkyu, 2021)
Particle shape of a non-spherical particle (clump) was reconstructed with the application of X-ray computed tomography (μCT). Shapes of the generated clumps were quantitatively estimated and correlated with the number of spheres (Ns). Subsequently, granular assemblies were prepared using these clumps in DEM simulations. After isotropic consolidation, the void ratio (e0) and mean coordination number ( ) of granular assemblies were correlated with Ns and overall regularity (OR), respectively. The DEM results found Ns=25 for clumps is sufficient to represent the real particle shapes. Meanwhile, e0 and were found to decrease with the increase of OR</i